The strategic importance of BRICS in the perception of countries seeking to join (قضايا سياسية, 2023)
The BRICS countries seek to change the current international order through economic means that would lead to a change in the nature of power and the pattern of its distribution at the global level, The BRICS group strengthens its economic policy in accordance with the group's shared interests. After the military alliances proved unsustainable, except for NATO, many of these countries see that the existing global economic system is unfair and sought other alternatives. Accession to the BRICS group means joining an economic not a political alliance, however, the increase in economic cooperation will affect the political sphere.